Reactions to sexual harassment of the physiotherapist - L. Bütow-Dûtoit; C.A. Eksteen; M. De Waal (AOSIS, 2008)
This  paper follows on a previous paper describing a studyconducted on sexual harassment in the physiotherapy work environment inSouth Africa. A survey questionnaire was used to determine the reactions ofphysiotherapists  after  they  experienced  their  worst  incidents  of  sexualharassment. The most common method of handling the sexual harassmentwas to avoid the perpetrator or situation. The most common effects relatedto work performance after the sexual harassment had occurred, were adecrease in concentration, job pleasure and confidence in job performanceand the most common emotional effect experienced was anger.